Clientelism Politics of Muslim Politician Who Became People’s Representatives - Mohammad Hidayaturrahman; Doli Witro; Ahmad Hasan Ubaid; Tamrin Tamrin; Anak Agung Sugiantiningsih (International Journal Ihya' 'Ulum al-Din, 2021)
People’s representatives are elected through general elections to represent the people fighting for the people's interests and aspirations. However, in practice, muslim politician who became people's representatives often represent themselves and their groups rather than represent those who have chosen them. This research was conducted to reveal how muslim politician who became people's representatives' actions the correlation between clientelism politics in managing the budget function. This descriptive qualitative research method collects data through direct observation in the field and in-depth interviews with various informants related to the research. The theory used in this research is political clientelism theory. From the research results, muslim politician who became people's representatives fight for the community's aspirations to escort a grant program to community groups, social assistance, and empowerment. The program is directly related to the winning team and supporters of voters in the previous elections. The program is intended to maintain the people's voting base and the granary in the next election. This is how the people's representative uses the parliament's existence and potential for electoral interests.